ความฉลาดทางอารมณ์ของนิสิตคณะทันตแพทยศาสตร์ มหาวิทยาลัยนเรศวร - สุภาพร แสงอ่วม (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
The purpose of this cross-sectional descriptive study was to explore the levels of the emotional intelligence and its associated factors. The sample included 302 dental students at Naresuan University in 2006 academic year. The instruments used in this study were questionnaires on demographic information, family information and social information, Thai Mental Health Indicator (TMHI-15) and Thai Emotional Intelligence Screening Test. The data were analyzed using descriptive statistics, independence t - test, one-way ANOVA, Pearson Correlation and multiple linear regression as appropriate. The results revealed that the mean total scores of emotional intelligence and the mean scale scores were within the normal range for Thai population. The emotional intelligence scores of the preclinical students were significantly higher than the clinical students (p is less than 0.05). Factors associated with emotional intelligence were the academic year, having reading and gardening as hobbies, participating in university activities, peer relationship and mental health status. The findings can be applied for the promotion of emotional intelligence and extracurricular activities for dental students.